Response of Soybean (Glycine max) to Soil and Foliar Applied Boron at Different Rates - Cirak, Cuneyt; Odabas, Mehmet Serhat; Kevseroglu, Kudret; Karaca, Emel; Gulumser, Ali (Indian Counc Agricultural Res, 2006)
An experiment was conducted to examine the effect of soil and foliar application of boron (66.14 % B 2 0) at different rates (0, 0.5, 1, 1.5 and 2 kg/ha) on plant height, first pod height, pod/plant, boron content of seed, germination rate, 1000 seed weight, oil, protein and ash content of seed and yield of 'A 3935' soybean (Glycine max (L.) Merr.) during 20022003 at experimental area of Black Sea Agricultural Research Institute. The experimental design was a randomized complete block in split plot arrangement with 3 replications utilizing application methods as main plot and boron rates as subplots. Increasing boron rates applied either soil or foliar improved yield (40 %), first pod height (17 %), boron content of seed (42 %), germination rate (11 %) and 1000-seed weight (5 %) of soybean. For maximum yield, 1.09 kg/ha rate of boron was recommended.
Keywords: Soybean; Boron; Fertilization; Soil Application; Foliar Application